2016
DOI: 10.1016/j.envres.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pre-existing health conditions on short-term mortality risks of temperature: Evidence from a prospective Chinese elderly cohort in Hong Kong

Abstract: Elders with pre-existing health conditions were more vulnerable to excess mortality risk to hot and/or cold temperature. Preventative measures should target on elders with chronic health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 60 publications
(68 reference statements)
3
18
1
Order By: Relevance
“…At lag slice 7, in lag 0–15 as in Figure 1, most of the cities have greater risks in both the extreme and moderate low temperature percentiles. These results are similar to the studies in China [17,18,19]. The physiological mechanism of the increased risk of low temperatures on diabetes remains unclear.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…At lag slice 7, in lag 0–15 as in Figure 1, most of the cities have greater risks in both the extreme and moderate low temperature percentiles. These results are similar to the studies in China [17,18,19]. The physiological mechanism of the increased risk of low temperatures on diabetes remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we have observed that the effects of temperature on diabetes are higher in extreme temperatures as seen in Table 2, which are consistent with literature [23,25,27]. The mechanism related to the increased risk in high temperatures among diabetics can be linked to the abnormalities of the thermoregulatory capacity caused by autonomic neuropathy [17,18,37]. Autonomic neuropathy is a potentially lethal diabetic complication, which affects multiple organ systems and of different clinical manifestations, with severe consequences such as hypoglycemia unawareness and cardiovascular dysfunction [38,39,40,41].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations